Injuries in Quidditch: A Prospective Study from a Complete UK Season - Rachel Pennington; Ashley Cooper; Alastair C Faulkner; Alasdair MacInnes; Thomas S W Greensmith; Alistair I W Mayne; Peter S E Davies (North American Sports Medicine Institute, 2021)
# Background Quidditch is a mixed-gender, full-contact sport founded in the USA in 2005, played worldwide by an estimated 25,000 players. It is one of the few mixed-gender full-contact sports, yet there remain few published studies regarding injury rates and patterns. A previous study suggested that the overall rate of injury in quidditch is in line with other contact sports, however raised concerns that female players were sustaining a higher rate of concussion when compared to male players. # Purpose To examine injury rates and injury patterns in UK quidditch athletes over the course of a single season. # Study design Prospective epidemiological study # Methods Data were prospectively collected by professional first aid staff for the 2017-18 season spanning all major UK tournaments, involving 699 athletes. Anonymized player demographics were collected by an online survey. Time loss injury rates were measured per 1000 athletic exposures (AEs) and hours of play. # Results The overall time loss injury rate was 20.5 per 1000 hours or 8.0 per 1000 AEs. The combined rate of concussion was 7.3 per 1000 hours or 2.8 per 1000 AEs. There was no statistical difference between time loss injuries in males (20.9/1000 hours and 8.1/1000 AEs) and females (13.9/1000 hours and 5.4/1000 AEs) (p=0.30) and no statistical difference between concussion rates in males (n=7) and females (n=4) (p=0.60). # Conclusions Total time loss injury rates in quidditch appear to be comparable with other full-contact sports such as football. The rate of concussions for both males and females appear higher when compared to other contact sports. # Level of evidence 3